An Examination of the Relationship between Service Quality Dimensions, Overall Internet Banking Service Quality and Customer Satisfaction (International Journal of Scientific Research and Management (IJSRM), 2015)
The focus on new technologies in all sectors is growing and Banking Industry is also not an exception to it. Internet Banking has the potential to transform the banking business as it significantly lowers delivery and transaction costs. Therefore it is essential for banks to know about the customer adoption of Internet Banking service & their satisfaction level for the same. Despite the importance of Internet banking in many financial institutions, fewer studies have focused on consumer adoption and customer satisfaction especially in the Indian setting. With technology implementation, a new phenomenon in Agra’s (Uttar Pradesh) banking sector , many customers has not yet embraced it. This study evaluates major factors (i.e. service quality, brand perception and perceived value) affecting on customers’ satisfaction in internet banking service settings. This study further evaluates influence of service quality on brand perception, perceived value and satisfaction in internet banking. The data was collected through customers’ survey and the collected data was analyzed using principle component (PCA) using SPSS 19.0. A result indicates that Perceived Value, Brand Perception, Responsiveness, Merchandising, Reliability, Trust/Security, Website design and Easy to Use are important factors in customers satisfaction in internet banking. Website design, Easy to Use, Merchandising, Responsiveness and Search option are predictors of brand perception in internet banking and Customised products, Convenience, Website design, Easy to Use, Reliability, Trust/Security, Responsiveness and Search option are predictors of perceived value in internet banking.